Implementing Educational Programs by LAZISMU DIY to Enhance Education in Indonesia: A Qualitative Analysis - Saputra, Dendi (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2024)
Purpose – This study aims to describe the implementation of educational programs by LAZISMU DIY in improving education in Indonesia, focusing on the effectiveness and efficiency of these philanthropic initiatives in enhancing community welfare in the Special Region of Yogyakarta. Design/methods– Employing a qualitative-descriptive research design, data were collected through observation, semi-structured interviews, and documentation. The tools and technologies used included digital recording devices, notebooks for field notes, and cameras for photographic documentation. Data analysis involved transcription, data reduction, and the identification of key themes and patterns. Findings – The findings reveal that LAZISMU DIY's programs, including scholarships and teacher training, significantly impact educational quality and access. These programs address financial barriers and promote sustainable educational development through a holistic approach combining financial aid and capacity-building activities. Research implications/limitations Despite the qualitative nature of the study limiting generalizability, the results highlight the potential of strategic philanthropic interventions in fostering educational equity. Future research should incorporate quantitative methods to validate these findings and explore long-term impacts Practical implications – The study emphasizes the importance of combining financial support with capacity-building and community engagement for effective educational interventions. This model provides a blueprint for other philanthropic organizations aiming to improve education in similar contexts. Originality/value – This study provides valuable insights into the successful integration of financial aid, capacity-building, and community engagement by LAZISMU DIY, showcasing its significant contributions to improving education in Yogyakarta and offering a replicable model for educational philanthropy.